Diversitas dan Inklusi dalam Lingkungan Digital: Memastikan Inklusi dalam Konteks Pekerjaan Jarak Jauh, serta Mengatasi Bias Teknologi - Dewi Dilasari; Julaika Pertiwi; Nauval Arfi Khaula; Nichlah Mufidah; M Isa Anshori (STIKes Ibnu Sina Ajibarang, 2023)
Purpose-This research aims to find out how to implement diversity and inclusion in the digital environment (1) Understand the concept of remote work (2) Find solutions to overcome technology bias (3). Digital/methodology/approach-In completing this paper we used the Literature Review method to make it easier to prepare the article and clarify the authenticity of the sources obtained. Findings-The research conducted was more specific through the external context compared to intrinsic values. This happens because many incidents in the discovery are covered in a subjective discussion and are accompanied by various realities of digitalization events and obstacles that are the main object. This discovery is the answer to everything directly related to diversity and inclusion in the digital sphere. Original/value-This paper covers the literature review by conveying the topics discussed, but also covers more broadly with many thoughts that are in line with the topics discussed regarding digital diversity and inclusion. Coupled with experience as a technology user who also feels the same way during the process of using it.